2007
DOI: 10.1029/2006je002787
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of processes responsible for Martian impact crater “layered ejecta structures” emplacement

Abstract: [1] We utilized images and stereo-derived topographic data acquired by the High Resolution Stereo Camera (HRSC) and Thermal Emission Imaging System (THEMIS) images together with other data in order to study the geology of ''layered ejecta structures'' associated with relatively pristine Martian impact craters. The geomorphology and morphometric properties indicate their origin as complex combinations of a variety of impact processes. The studied (inner) layered ejecta structures often exhibit ground-hugging ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 65 publications
(108 reference statements)
1
63
0
1
Order By: Relevance
“…Furthermore, their modeling predicted that dissipation of some of the impact energy as heat would result in temperatures well above the melting point of subsurface volatiles such as water ice; this would provide additional vapor and increase the strength of the dispersive effect of the expanding plume. It should be noted that the morphology of the low-temperature haloes does not, we feel, require suspension and transportation of ejecta by water or ice as has been invoked for formation of layered ejecta lobes (e.g., Komatsu et al, 2007;Senft and Stewart, 2008). However, the presence of water in the vapor plume could, as suggested by Wrobel et al (2006), result in an erosion-resistant armor that might account for the persistence of low-temperature haloes for long periods of time.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, their modeling predicted that dissipation of some of the impact energy as heat would result in temperatures well above the melting point of subsurface volatiles such as water ice; this would provide additional vapor and increase the strength of the dispersive effect of the expanding plume. It should be noted that the morphology of the low-temperature haloes does not, we feel, require suspension and transportation of ejecta by water or ice as has been invoked for formation of layered ejecta lobes (e.g., Komatsu et al, 2007;Senft and Stewart, 2008). However, the presence of water in the vapor plume could, as suggested by Wrobel et al (2006), result in an erosion-resistant armor that might account for the persistence of low-temperature haloes for long periods of time.…”
Section: Discussionmentioning
confidence: 98%
“…However, we observe low-T haloes for craters with a range of ejecta morphologies, indicating that emplacement of low nighttime temperature materials is not restricted to DLE craters. Komatsu et al (2007) examined a number of different types of layered ejecta structures and observed that the outer layers are sometimes cooler at night than inner layers. Though all of these studies observe morphological characteristics that suggest particle size variations within ejecta deposits, none has specifically examined the low-T haloes described here.…”
Section: Low Nighttime Temperature Haloes On Marsmentioning
confidence: 99%
“…It is widely accepted that layered ejecta deposits were highly fluidized at the time of their emplacement and occurred as relatively thin groundhugging flows (Carr et al, 1977). Contrasting models have been proposed to account for these layered ejecta on Mars: the interaction of ballistic ejecta with a volatile-rich vapor plume (Carr et al, 1977), interaction with the Martian atmosphere (Schultz and Gault, 1979), or a combination of the two (Barlow, 2005;Komatsu et al, 2007).…”
Section: Marsmentioning
confidence: 99%
“…Cross-cutting relationships indicate that the giant polygons predate the formation of mesas and bright-colored mounds. Mounds do not seem to be confined to the immediate vicinity of impact craters; therefore, an origin other than shock-induced liquefaction (Komatsu et al, 2007c) has to be invoked for some, if not all of these mounds. Rampart craters are considered further indicators of an ice-rich substratum (Costard and Kargel, 1995).…”
Section: Further Evidence Of Fluid and Volcanic Activitymentioning
confidence: 99%
“…They found that mud volcanism and deposition around geysers and springs were most consistent with their observations. Komatsu et al (2007c) proposed that at least some of the bright mounds found at Acidalia and elsewhere on Mars may have been produced by liquefaction due to impact-induced shockwaves. According to McGowan (2009), mounds at Cydonia Mensae could be mud volcanoes produced by the release of underground methane and/or CO 2 gas.…”
Section: Martian Landforms Indicative Of a Fluid-rich Substratummentioning
confidence: 99%